ASC annual report 1997/98 (Annual report Australian Sports Commission, 1998)
The Annual report 1997/98 of the Australian Sports Commission. Summary of compiance: Advertising and market research, Auditors report , Audit Committee report, ASC contact officer, Board membership and terms of appointment ,Corporate overview, Divisional performance reports, Enabling legislation, Enterprise Agreement, Equal Employment Opportunity, Financial and staffing resources summary, Financial statements, FOI officer and documentation, Industrial democracy, Internal and external scrutiny, Occupational health and safety, Responsible Minister, Staffing organisational chart and senior executive staff, Staff overview, Social justice and equity